Effects of extrusion on nutritional and non-nutritional properties in the production of multigrain ready to eat snacks incorporated with NUA45 beans - Andirigu, Arlene Rachel; Nyanga, Loveness Kuziwa; Chopera, Prosper Kujinga (The North African Journal of Food and Nutrition Research, 2023)
Background: Extrusion technology, used in producing a variety of food products, including ready-to-eat snacks, has become a popular and reputable industrial method. Snacks have been occupying an important part of the diet for the world's population. However, the effects of extrusion on nutritional and non-nutritional properties in the production of snacks using traditional grains incorporated with legumes are not fully understood. Objective: To determine the effects of extrusion on nutritional and non-nutritional qualities of multigrain puffs from white sorghum, pearl millet and NUA45 beans. Methods: White sorghum, pearl millet and NUA45 beans were blended in the ratios 50:30:20, 50:20:30 and 50:10:40% to select the best composite for snack production. Selected nutritional and non-nutritional quality parameters were compared before and after extrusion.  Results: The extrusion process caused a significant increase (p < 0.05) in the content of fat (2.22 to 2.61%, 1.73 to 2.40 and 2.75 to 3.29% for the blends 1, 2 and 3 (50:30:20, 50:20:30 and 50:10:40% respectively), while causing a decrease in protein content, 14.44 to 13.34%, 16.63 to 13.34% and 20.56 to 16.41% in the multigrain puffs. Extrusion also increased iron, zinc and sodium content significantly (p < 0.05) while decreasing calcium. Magnesium and phosphorus had no change. Furthermore, extrusion improved the multigrain puffs' nutritional value and antioxidant activity.  The extrusion process caused a significant decrease in tannins (6.82 to 6.01%, 7.82 to 2.17% and 5.74 to1.17%) and phytates contents (2.82 to 2.43%, 3.01 to 1.55% and from 2.92 to 0.37%) of the resultant multigrain puffs from blends 1,2 and 3 respectively.  Total phenolic content increased (18.56 to 172.22, 24.38 to 144.61, and 65.87 to 180.44 mg GAE/100g). Conclusion:  Extrusion enhances selected nutrients while decreasing anti-nutrients. Based on the composite feeds of white sorghum, pearl millet and NUA45 beans analyzed, the composite blend in the ratio 50:10:40% can be used to develop an acceptable novel healthy extruded traditional grain-based snack.Keywords: extrusion, ready-to- eat snacks, multigrain puffs, nutrients, anti-nutrients, white sorghum, pearl millet, NUA45 beans.